The Capitalization Training for MSMEs Actors in Waringin Jaya Village, Bojonggede Subdistrict, Bogor Regency - Ruhiyat, Endang; Sugiyanto, Sugiyanto; Sukmana, Eka; Mariati, Mariati; Hayati, Siti; Muliawati, Kristina Ika (The Future of Education Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, contributing significantly to GDP and employment. However, MSMEs, particularly in West Java Province, still face serious challenges, particularly related to financial management and access to capital. Many MSMEs fail due to limited capital and knowledge in financing and preparing simple financial reports. Adequate financial reports are essential for obtaining financing and business expansion. This Community Service (PKM) activity aims to increase the scale of MSME businesses in Waringin Jaya Village, Bojonggede District, Bogor Regency, by providing assistance in accessing capital and preparing simple financial reports. The PKM implementation method involves an initial survey to identify MSME needs, followed by direct assistance using a prepared module. This assistance is divided into four sessions: an explanation of capital access requirements, preparing simple financial reports, preparing simple sales reports, and a question and answer session. The results of the activity indicate that MSMEs gain a better understanding of credit requirements, capital sources, and how to prepare efficient financial reports and simple sales reports. The positive response from participants indicated that the information and insights provided were very helpful in developing their businesses. It is hoped that this increased understanding will facilitate MSMEs' access to capital, enable business expansion, create new jobs, and ultimately support local economic growth.